Protective factors in the attainment of resilience in persons with disability - Wiwin Hendriani (Masyarakat, Kebudayaan dan Politik, 2018)
People who live with a physical disability requires further attention. Living as a disabled person is not easy, especially if the individual was born as a normal person. This study aims to identify the protective factors that play an inﬂuential role in the attainment of resilience in individuals who experience physical changes as a disabled person. This research applied the instrumental case study approach. The participants consisted of eight individuals with physical disabilities. The data was gathered using an in-depth interview, while the thematic analysis technique was used in the data analysis. The results show that there were eight protective factors involved in achieving resilience in individuals who experience physical change as a disabled person. The eight factors consist of four external protective factors; social support, psychological intervention, the presence of a source of inspiration and the availability of public facilities for persons with disabilities. There are also four internal protective factors, namely religiosity, the willingness to learn, an awareness of social support, and an awareness of self-identity. The results of this study can be implemented in order to assist in the attainment of resilience among other groups of individuals who also undergo a change of physical condition through the strengthening of the eight protective factors.